Method for studying the photostability of solar cells based on organic-inorganic perovskites using a confocal spectrometer - Mahon, Natallia S.; Korolik, Olga V.; Mazanik, Alexander V. (Journal of the Belarusian State University. Physics, 2022)
A method for studying photosensitive structures using the example of studying the photodegradation and dark recovery of organic-inorganic perovskite solar cells is present. The method is based on the use of a confocal spectrometer to measure Raman spectra, photo- and electroluminescence spectra and kinetics, the kinetics of the short-circuit current and the open-circuit voltage under local exposure to monochromatic radiation. Raman spectra make it possible to establish the presence or absence of secondary phases, the formation of which is possible in photosensitive layers under the influence of light. The photoluminescence spectra enable to reveal the single-phase nature of the object under study. Mapping the intensity and position of the center of mass of the photoluminescence band in the plane of the object makes it possible to judge the spatial arrangement of the centers of non-radiative recombination of charge carriers, the distribution of the regions with the highest and lowest efficiency of the extraction of charge carriers by transport-acceptor layers and the spatial homogeneity of the chemical composition. Comparison of the electroluminescence spectra before and after light exposure allows revealing the formation of non-radiative recombination centers in the photoabsorbing layer and at interfaces with the transport layers. Analysis of the kinetics of changes in the parameters of the photoluminescence band obtained by measuring the short-circuit current and the open-circuit voltage makes it possible to establish the dominant photoinduced processes leading to a change in the intensity of the photoluminescence band.